2020
DOI: 10.1002/pbc.28396
|View full text |Cite
|
Sign up to set email alerts
|

Reducing acute kidney injury in pediatric oncology patients: An improvement project targeting nephrotoxic medications

Abstract: Background Nephrotoxic medication exposure and associated acute kidney injury (AKI) occur commonly in hospitalized children. At Cincinnati Children's Hospital Medical Center, there is an initiative to increase awareness of nephrotoxic medication exposure and decrease rates of associated AKI. The oncology service utilized these data in a quality improvement project to drive reductions in AKI rates. Methods Three interventions were implemented targeted at decreasing the incidence of nephrotoxic exposure, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…This finding justifies the current attempts to prevent renal injury or at least to minimize the impact of potential nephrotoxins on the kidney. The reduction of nephrotoxic exposure is one of the effective tools already used in oncological patients [ 30 ]. The animal models suggest the possibility to prevent AKI with the use of phosphodiesterase-5 inhibitors prior to potentially nephrotoxic treatment [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding justifies the current attempts to prevent renal injury or at least to minimize the impact of potential nephrotoxins on the kidney. The reduction of nephrotoxic exposure is one of the effective tools already used in oncological patients [ 30 ]. The animal models suggest the possibility to prevent AKI with the use of phosphodiesterase-5 inhibitors prior to potentially nephrotoxic treatment [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 A subsequent multicenter study featuring nine large children's hospitals from across the country observed a significant and sustained lowering of 24% in rates of nephrotoxic AKI. 12 Because of these studies, use of NINJA is becoming increasingly used among pediatric patients, including in the neonatal ICU, 13 in children with cystic fibrosis, 14 in pediatric oncology, 15 and in the bone marrow transplant unit. 16 The success of the NINJA program in the pediatric population has prompted calls from the American Society of Nephrology and others for further validation in adult populations.…”
Section: Introductionmentioning
confidence: 99%
“…Susceptibility to perioperative AKI is multifactorial, with previously reported risk factors of younger age, pre‐existing renal insufficiency, duration of cardiopulmonary bypass (CPB), pre‐ and postoperative low cardiac output and fluid overload, and exposure to nephrotoxic agents 2,9,12–14 . As such, quality improvement (QI) efforts to reduce the incidence and severity of AKI have focused on risk assessment, timely diagnosis, optimization of hemodynamics, and avoidance of nephrotoxic agents 15–23 …”
Section: Introductionmentioning
confidence: 99%
“…2,9,[12][13][14] As such, quality improvement (QI) efforts to reduce the incidence and severity of AKI have focused on risk assessment, timely diagnosis, optimization of hemodynamics, and avoidance of nephrotoxic agents. [15][16][17][18][19][20][21][22][23] Given its impact on renal health and patient outcomes, our team developed a multi-pronged QI clinical pathway to reduce AKI incidence after HT that included perioperative aminophylline use, optimization of postoperative renal perfusion pressure, and avoidance of nephrotoxic medications. We hypothesized that implementation of a standardized clinical pathway would result in reduced incidence and severity of AKI in patients undergoing HT.…”
Section: Introductionmentioning
confidence: 99%